Servitude with a smile: An anti-oppression analysis of emotional labour - Patricia Chong (International Labour Organization (ILO), 2009)
With the rise of the service society, emotional labour has become increasingly prevalent. Emotional labour involves the production and consumption of the worker's identity as part of the customer service experience. However, emotional labour requires the performance of appropriate or moral roles, as determined by one's identity within interlocking gender, race and class hierarchies. Hence, there are different behavioural expectations depending on who is doing the emotional labour. These different expectations are based on `social norms' which construct identities in such a way that privilege some at the expense of subordinating others. Hence, emotional labour is not a neutral act since it has the effect of naturalizing inequalities on an individual level and thus justifying oppression at large. This naturalization process also takes place at the institutional level which has largely been ignored by much of the academic literature on emotional labour. In answering the question of how emotional labour reinforces intersecting systems of gender, race and class oppression, this paper argues that emotional labour makes these inequalities appear `natural' on both the individual and the institutional level. As such, this paper primarily focuses on the institutional level of this naturalization process.
Keywords: 330